Effect of thin capitalization and transfer pricing on tax avoidance on manufacturing sector multinational company listed on the indonesia stock exchange for the period 2016-2021 - Dina Khairuna Siregar; Fitri Nur Rahman; Detty Susilawati (Junal Ilmu Manajemen, 2023)
The purpose of this study was to determine the effect of thin capitalization and transfer pricing on tax avoidance in the multinational manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2021 period partially and simultaneously. The research method used in this study is descriptive with a quantitative approach. The population in this study is the multinational manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2021 period which amounted to 45 companies. The number of multinational manufacturing companies that were sampled in this study was 16 companies. The total sample of research is 96 samples The conclusion of this study is partially thin capitalization has no effect on Tax Avoidance, Transfer Pricing affects Tax Avoidance. Simultaneously Thin Capitalization and Transfer Pricing affect Tax Avoidance.